2020
DOI: 10.3390/microorganisms8020146
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Modulates Swine Gut Microbiota and Improves Growth Performance of Nursery Pigs When Combined with Peptide Cocktail

Abstract: Zinc has been very efficacious in reducing post-weaning diarrhea, whereas animal-derived peptides are suggested to improve the growth performance of weaned piglets. However, the combined effect of zinc and peptides on swine production and swine gut microbiota is still largely unknown. In this study, we followed 288 nursery pigs from the age of d30 to d60 to evaluate the growth performance and gut microbiota of weanling pigs subjected to different levels of a fish-porcine-microbial peptide cocktail (0.05%, 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 72 publications
6
19
0
Order By: Relevance
“…The intestinal microbiota assists the host in energy absorption, epithelium development, immune system enhancement, pathogen inhibition, and the fermentation of non-digestible foods to short-chain fatty acids (SCFA) and other metabolites [41,42]. In the present study, Firmicutes and Bacteroidetes were the two most predominant phyla in the piglet gut microbiota, which was consistent with our previous piglet studies [43][44][45][46]. Similarly, as in our previous reports, Prevotella and Lactobacillus were the abundant genera in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The intestinal microbiota assists the host in energy absorption, epithelium development, immune system enhancement, pathogen inhibition, and the fermentation of non-digestible foods to short-chain fatty acids (SCFA) and other metabolites [41,42]. In the present study, Firmicutes and Bacteroidetes were the two most predominant phyla in the piglet gut microbiota, which was consistent with our previous piglet studies [43][44][45][46]. Similarly, as in our previous reports, Prevotella and Lactobacillus were the abundant genera in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary intervention has become a very important focus within the swine industry to help minimize the detrimental effects of weaning [ 10 , 19 , 29 , 30 ]. The current study characterized the capabilities of probiotics and lactylates on growth performance, feed efficiency, peripheral blood cell counts, and gut microbiota changes during the nursery stage.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary energy contributes to the greatest proportion of feed cost in the swine industry [ 9 , 10 ]. In addition to carbohydrates and fat from grain, dietary fat and oils are major energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the swine gut microbiome correlated with feed efficiency, fat deposition, and growth performance. [6][7][8][9][10] Despite this progress toward understanding the swine gut microbiome, many important ecological questions are yet to be answered.…”
Section: Introductionmentioning
confidence: 99%